WANPRESTASI OLEH PERUSAHAAN PIALANG BERJANGKA TERHADAP INVESTOR DALAM TRANSAKSI FOREX MARGIN TRADING PADA BURSA BERJANGKA (Putusan PN SURABAYA Nomor 65/Pdt.G.S/2020/PN Surabaya) - Muh Kevin Fajri Tobing; Benni Rusli; Anggun Lestari Suryamizon (UNES Law Review, 2023)
Humans have always traded with other humans around them for various reasons with the barter system. Along with the development of the era and civilization, this barter system was no longer used because it had many weaknesses, so a new payment system was invented, namely using money as a medium of exchange and payment. The payment system using money is also not without weaknesses in its function for transactions with other countries that have different types of currencies. World trade transactions in this era of globalization are closely related to foreign currency trading, which is commonly called currency or foreign exchange (forex). Foreign Exchange stands for forex (foreign exchange) includes two meanings, namely foreign currency and the process of exchanging from one currency to another. Moreover, the customer does not meet face to face and is at risk of default, misuse of the customer's margin. In this writing, the author raises several problems of default. This research is descriptive in nature and aims to obtain a complete description of the legal situation in force in a particular place. Normative juridical law research is the collection of material or research materials aimed at written documents. Sources of data and legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. This research uses document studies related to laws and regulations, books and journal judge decisions related to default. The results of this study are important for investors to understand that the legal process can take significant time and costs. In addition, success in suing a futures brokerage company depends on the strength of the evidence it has and also on the legal provisions in force in the local jurisdiction. Therefore, it is important for investors to always be careful in choosing a trusted futures brokerage company, and to ensure that there is a written agreement and adequate protection guarantees before making a forex margin trading transaction. The form of CoFTRA coaching is the provision of training for Futures Trading actors to increase knowledge/expertise in Commodity and Futures Trading. The form of preventive supervision is that CoFTRA conducts field supervision and carries out periodic and/or occasional reports by Futures Brokers regarding their activities on the Futures Exchange and the number and customer data received online, and the implementation of a Single Supervision System for market integrity and trading actors Futures connected online and real time.